Oxidation behavior and kinetics of ZrB2 containing SiC chopped fibers. Issue 16 (December 2015) - Silvestroni, Laura; Landi, Elena; Bejtka, Katarzyna; Chiodoni, Angelica; Sciti, Diletta
Highlights: The oxidation of a ZrB2 -composite with short SiC fibers is studied by TG at 1200–1500 °C. The oxidation kinetics obeys a linear law with activation energy above 253 kJ/mol. Degradation mechanisms up to 1650 °C for 5–30 min are studied using a bottom-loading furnace. Comparisons among the addition of short SiC fibers, particles and whiskers are discussed. Tyranno SA3 fibers provide higher toughness to ZrB2 and better oxidation resistance than SiC particles. Abstract: The oxidation of ZrB2 toughened with SiC short fibers has been evaluated in a thermo-gravimetric analyzer from 1200 to 1500 °C for 10 h and in a bottom-up loading furnace up to 1650 °C for 5–30 min. The microstructure has been investigated by SEM and TEM. The oxidation kinetics, after a transient stage, follows a linear behavior, indicating that the outer oxide layer is not protective above 1400 °C. Fibers notably oxidize above 1500 °C with formation of silica glass and a carbon-rich phase. Mechanisms of SiC fiber oxidation and formation of the various scales are proposed for the various temperature ranges. Comparisons with the oxidation of ZrB2 containing SiC in form of particles, whiskers and previous generation fibers are also discussed.